Study of B±,0 → J/[psi]K+K−K±,0 and search for B0 → J/[psi phi] at BABAR - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We study the rare B meson decays B±,0→J/ψK+K−K±,0, B±,0→J/ψϕK±,0, and search for B0→J/ψϕ, using 469×106 B¯B events collected at the Υ(4S) resonance with the BABAR detector at the PEP-II e+e− asymmetric energy collider. We present new measurements of branching fractions and a study of the J/ψϕ mass distribution in search of new charmonium-like states. In addition, we search for the decay B0→J/ψϕ and find no evidence of a signal.